Pengaruh Penggunaan Ulang Copper Slag Pada Proses Blasting Terhadap Kekasaran Permukaan Pelat Badan Kapal - Muhammad Ilham Dermawan; Tri Agung Kristiyono Tri; Bagus Kusuma Aditya; Nur Yanu Nugroho; Bagiyo Suwasono (Departemen Teknik Kelautan Universitas Hasanuddin, 2026)
The blasting process in the shipping sector aims to remove dirt, rust and factory scale from the plate surface and to create roughness on the surface so that the paint layer can adhere well. In the blasting process, abrasive materials are generally used once or twice. However, in field practice, reused copper slag has been used as an abrasive material. This study aims to analyze the surface roughness level of the plate during the blasting process using the Analysis of Variance (ANOVA) method with variations of new copper slag, reused copper slag 1 and 2 with cleanliness standards according to ISO 8501-1 SA 2.5 and the standard surface roughness level of the plate according to IMO-PSPC (Performance Standard for Protective Coatings) with a surface roughness level ranging from 35 µm – 75 µm. From the results of the data analysis, it shows that the reuse of copper slag during the blasting process, the roughness level obtained is getting smaller. Therefore, the surface roughness level of the plate that meets the IMO-PSPC standard which ranges between 35µm-75µm is copper slag reuse 2 and while the maximum limit of the surface roughness level of the plate that meets the IMO-PSPC criteria is copper slag reuse-3.